DEVELOPMENT OF A PROFESSIONAL TRAINING COURSE TO ENHANCE PJBL COMPETENCIES OF TEACHERS AT A TECHNICAL UNIVERSITY - Gradaleva, Ekaterina; Polukhina, Marina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The research is aimed at designing a professional development course where special emphasis is laid upon teacher preparation for international project activities. A poll has been conducted to find out whether technical university teachers are inclined to using project-based learning (PJBL) in the classroom. It shows that in reality most of them don’t have a holistic view of the approach. They mention the lack of a methodological base, language skills and ICT practice to integrate innovative techniques into their teaching. It becomes obvious that there is a need to rethink the design of teacher preparation to cultivate educators who are able to demonstrate PJBL practices and be effective in preparing students for the project-based world. To better understand the ways of orienting teachers toward the project-based approach a set of teacher competencies has been specified. It comprises motivation, personal qualities and models of behavior that help an educator make the transition to new methods of teaching, methodological knowledge, XXI century skills (critical thinking, creativity, collaboration, communication, problem-solving, decision making), transnational communicative competencies (linguistic, rhetoric, cultural, media). These components serve as a basis for the professional development course content. As a result, it is proposed to include three major units for training: PJBL Methodology; Professional English and Intercultural Communication; Information and Communication Technologies.